A nationally representative study of the association between communication impairment at 4-5 years and children's life activities at 7-9 years - McCormack, J.; Harrison, L.; McLeod, S.; McAllister, L. (My University, 2011)
Purpose: To examine the longitudinal association between communication impairment (primary or secondary diagnosis) and children's Activities and Participation (International Classification of Functioning, Disability and Health--Children and Youth [ICF-CY]; World Health Organization [WHO], 2007). Method: Participants were 4,329 children in the Longitudinal Study of Australian Children (LSAC; Australian Institute of Family Studies [AIFS], 2009): 1,041 (24.0%) of these children were identified with communication impairment at 4-5 years of age, and 3,288 (76.0%) of these children were not identified with a communication impairment. At age 7-9 years, Activities and Participation (WHO, 2007) outcomes across 5 ICF-CY domains were provided by (a) teachers (Academic Rating Scales [National Center for Education Statistics (NCES), 2002], Approach to Learning Scale [Gresham & Elliott, 1990], School Progress Scale (AIFS, 2009), Strengths and Difficulties Questionnaire [SDQ; Goodman, 1997], and Student-Teacher Relationship Scale [Pianta, 2001]); (b) parents (School-Age Inventory of Temperament [McClowry, 1995] and SDQ); (c) children (Marsh Self-Description Questionnaire-III [Marsh, 1992], School Liking [Ladd & Price, 1987], and Bullying [Kochenderfer & Ladd, 1997]); and (d) child assessment (Peabody Picture Vocabulary Test--III: Adapted; Rothman, 2003). Results: Children identified with communication impairment at age 4-5 years performed significantly poorer at age 7-9 years on all outcomes. Parents and teachers reported slower progression in reading, writing, and overall school achievement than peers. Children reported more bullying, poorer peer relationships, and less enjoyment of school than did their peers. Analyses of covariance tests confirmed significant associations between communication impairment and outcomes, over and above the effects of sex, age, Indigenous status, and socioeconomic status. Conclusion: Consideration of the breadth and longevity of Activities and Participation outcomes reveals the potential extent and severity of communication impairment and directs future research and practice.
Journal of Speech, Language and Hearing Research
Keywords: Childhood and child development